Thai Undergraduates’ Explanation of their Learning and Performance Behavior: A Case in Educational Management - Phoewhawm, Ravee Art (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
This study examines the level of Thai undergraduate students’ learning and performance behavior and to provide an in-depth deep explanation on their phenomenon. Due to a very high percentage of response from a questionnaire revealing that most of these students tend to have an avoidance behavior in learning and performance this paper is ardent in offering an explanation on the performance and learning behavior of Thai undergraduates. The work is focused on finding the students’ causes of ‘mastery and performance avoidance goal’. The work also proposes the policies, practices and development in management for improving their learning and performance. A total of 240 undergraduate students took part in filling out the questionnaire. Findings reveal that mastery avoidance comes from a “difficulty of understanding, fear of asking questions, protecting the image, and feeling of shyness”. Performance avoidance is based on “shyness, protecting one’s image, procrastination, and just maintaining a certain grade”.